‘Run Silent, Run Deep’: Examining Right-Wing Extremism in the Military - Amarasingam, Amarnath (Perspectives on terrorism, 2024)
The threat posed by current or former members of the military joining right-wing extremist groups is an issue of growing concern - evidenced by arrests and disrupted terrorist plots across Western Europe and North America. Using interviews with individuals who are both former extremists and have military experience, this article provides a basis for understanding the ways in which military service intersects and interacts with far-right extremism. By focusing on what we term the operational dimensions of the overlap between right-wing extremism and the military service, this article advances a novel framework for understanding how right-wing extremists navigate military institutions, such as recruitment during and after service, and using both covert and overt measures to reveal or conceal their beliefs, as well as recruit others. This study also illustrates how the timing of military service can impact susceptibility or resilience to radicalisation based on specific unit dynamics and planned or unplanned exits from service. Finally, this article discusses how these findings can produce practical recommendations for military institutions, while highlighting the need for more research on the topic.